2013
DOI: 10.1172/jci66031
|View full text |Cite
|
Sign up to set email alerts
|

The genomics of schizophrenia: update and implications

Abstract: Schizophrenia is strongly familial yet rarely (if ever) exhibits classical Mendelian inheritance patterns. The advent of large-scale genotyping and sequencing projects has yielded large data sets with higher statistical power in an effort to uncover new associations with schizophrenia. Here, we review the challenges in dissecting the genetics of schizophrenia and provide an update of the current understanding of the underlying genomics. We discuss the breadth of susceptibility alleles, including those that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 99 publications
1
72
0
1
Order By: Relevance
“…The 15q11-13 locus has been identified in several CNV studies in SCZ as well as in a familial SCZ linkage study (Giusti-Rodriguez and Sullivan, 2013;Liao et al, 2012). Kohannim et al (2012) reported 22 genes associated with temporal lobe volume and among them were GABRG3 and MAGI2.…”
Section: Discussionmentioning
confidence: 99%
“…The 15q11-13 locus has been identified in several CNV studies in SCZ as well as in a familial SCZ linkage study (Giusti-Rodriguez and Sullivan, 2013;Liao et al, 2012). Kohannim et al (2012) reported 22 genes associated with temporal lobe volume and among them were GABRG3 and MAGI2.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some factors that are implicated in the development of psychosis that it does not incorporate. Psychosis has a strong genetic component ([119]), but the role of specific risk genes in the model has yet to be determined.…”
Section: To What Extent Do the Human And Animal Data Converge?mentioning
confidence: 99%
“…Onset is typically in late adolescence or early adulthood, but signs of dysfunction can be seen in an earlier prodromal phase . Based on the clinical progression and the 64-81% heritability of the disorder (Giusti- Rodriguez and Sullivan, 2013), a hypothesis emerged that schizophrenia's origins could be found early in development, long before the onset of symptoms (Weinberger, 1987). For more than 35 years, clinicians and scientists have searched for the biological foundations of an altered developmental trajectory that leads to the specific disease symptoms, but our understanding of this process is far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, genetic and environmental influences alone may confer risk for schizophrenia, but it appears that a combination of multiple factors is necessary for disease manifestation in most cases (Giusti-Rodriguez and Sullivan, 2013;Lewis and Levitt, 2002;Mowry and Gratten, 2013;Sullivan et al, 2003;Tsuang, 2000). Supported by expanded basic science efforts and increasingly sophisticated animal models, a unifying concept has emerged stating that many of these disparate risk factors converge onto common dysfunctional pathways and lead to illness de Jong et al, 2012;Mirnics, 2009, 2014b;Mirnics et al, 2006).…”
Section: Introductionmentioning
confidence: 99%